2023
DOI: 10.1111/1750-3841.16684
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of umami taste and their contributing compounds in edible fungi based on electronic tongue, sensory evaluation, and chemical analysis

Tao Feng,
Weitong Cai,
Da Chen
et al.

Abstract: Edible fungi are rich in nutrients and have unique umami taste, which varies with genotypes, growth conditions, and harvest time. In this study, umami compounds in 12 species of edible fungi are analyzed and identified by electronic tongue. Through principal component analysis and discriminant factor analysis, these 2 methods could be successfully distinguished the variety of 12 edible fungi. Besides, the umami intensity of edible fungi soup is also evaluated by sensory and chemical analysis methods, for examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…38 CC showed a satisfactory EUC value of 248.00% (2.48 g MSG per g dw), which indicated that it was suitable for use as a flavoring ingredient in food or as an additive to imbue nutritional food and functional food with an umami flavor. 43 Feng et al 97 also tested the EUC value of CC (2.10 ± 0.09 g MSG per g dw) as well as umami intensity based on electronic tongue (5.18 ± 0.17) and sensory evaluation (4.30 ± 0.27).…”
Section: Chemical Profiles Of Cantharellus Cibariusmentioning
confidence: 99%
“…38 CC showed a satisfactory EUC value of 248.00% (2.48 g MSG per g dw), which indicated that it was suitable for use as a flavoring ingredient in food or as an additive to imbue nutritional food and functional food with an umami flavor. 43 Feng et al 97 also tested the EUC value of CC (2.10 ± 0.09 g MSG per g dw) as well as umami intensity based on electronic tongue (5.18 ± 0.17) and sensory evaluation (4.30 ± 0.27).…”
Section: Chemical Profiles Of Cantharellus Cibariusmentioning
confidence: 99%